The impact of age within academic year on adult outcomes - Claire Crawford; Lorraine Dearden; Ellen Greaves (Institute for Fiscal Studies (IFS), 2013)
Children born at the end of the academic year have lower educational attainment, on average, than those born at the start of the academic year. Previous research has shown that the difference is most pronounced early in pupils' school lives, but remains evident and statistically significant in high-stakes exams taken at the end of compulsory schooling. Those born later in the academic year are also significantly less likely to participate in post-compulsory education than those born at the start of the year. We provide the first evidence on whether these differences in childhood outcomes translate into differences in the probability of employment, occupation and earnings for adults in the UK. We also examine whether there are differences in broader measures of well-being such as self-perceived health and mental health. We find that the large and significant differences observed in educational attainment do not lead to pervasive differences in adulthood; those born towards the end of the academic year are more likely to experience unemployment (which is particularly true for females and those that don't achieve a degree level qualification) but in general there are few substantial or statistically significant differences in terms of occupation, earnings and self-perceived health and mental health. It is not clear why this should be the case, but if employers reward productivity equally as they learn more about their workers, irrespective of their educational attainment, then this lack of significant differences may not be surprising.
Keywords: I21; J24; 330; month of birth; wages; employment; educational attainment